If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + 5(2x + -5) = -20 + -3x Reorder the terms: -8x + 5(-5 + 2x) = -20 + -3x -8x + (-5 * 5 + 2x * 5) = -20 + -3x -8x + (-25 + 10x) = -20 + -3x Reorder the terms: -25 + -8x + 10x = -20 + -3x Combine like terms: -8x + 10x = 2x -25 + 2x = -20 + -3x Solving -25 + 2x = -20 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -25 + 2x + 3x = -20 + -3x + 3x Combine like terms: 2x + 3x = 5x -25 + 5x = -20 + -3x + 3x Combine like terms: -3x + 3x = 0 -25 + 5x = -20 + 0 -25 + 5x = -20 Add '25' to each side of the equation. -25 + 25 + 5x = -20 + 25 Combine like terms: -25 + 25 = 0 0 + 5x = -20 + 25 5x = -20 + 25 Combine like terms: -20 + 25 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| 25x+8-28x=3-7 | | 18-3n=36-9 | | (-3ax^2)0= | | p^2-2p=3 | | 5x+8=21x | | 60=4 | | 10l=150 | | 2x+3=x^2 | | 2k=9 | | 2x+6=3x+13 | | 10-6(4+b)=b-14 | | 7x+5=10+2x | | 4x^2-28x+49=4 | | 7i+3=38 | | 4x^2-53x+130=0 | | 4y^2-48=0 | | 4f+5=f+11 | | 5(2x-2)-2(9x)=1 | | af+5=f+10 | | 49n^2-16=0 | | 3(-2)+2(-2)=-10 | | a-7=9 | | 10c=5 | | 2b=9 | | 3x^2-7x=-1 | | 9p-13p=24 | | 4x^2-4x+5=0 | | 7x+49=9x+36 | | 2(4a-8)+3=3a-6 | | z^2+5z=50 | | 2(v+7)=9v+42 | | 3y^2-8y=3 |